Preliminary study of transoral robotic surgery for pharyngeal cancer in Japan. Issue 1 (March 2016) - Fujiwara, Kazunori; Fukuhara, Takahiro; Kitano, Hiroya; Fujii, Taihei; Koyama, Satoshi; Yamasaki, Aigo; Kataoka, Hideyuki; Takeuchi, Hiromi
Abstract Transoral robotic surgery (TORS) with the da Vinci Surgical System has been used for the removal of pharyngeal and laryngeal cancers with the objective to improve functional and aesthetic outcomes without worsening survival. While TORS has been approved in many countries, Japan's FDA has not yet done so. Our hospital started using TORS with the approval of the Ethical Review Board and the Minimum Invasive Surgical Center Committee at Tottori University. No surgical outcomes of TORS for Japanese patients with head and neck cancer have been reported in Japan. This paper deals with the outcomes and feasibility of TORS for Japanese patients with pharyngeal cancer at our institution. TORS was performed for 10 patients with T1, T2, T3 oropharyngeal and hypopharyngeal squamous cell carcinoma between 2013 and 2014. This is a single-institutional study. TORS could be completed for all cases, except one patient that was not candidate, and no intraoperative conversion to an open surgical procedure was required. Five patients underwent neck dissection, two of them concurrent and three staged. Of all patients, positive surgical margins were detected in two. The average blood loss including neck dissection was 21.5 ± 33.4 ml, the operation time was 183 ± 36 min and the console time was 103 ± 22 min. No tracheostomy had been performed either pre- or postoperatively, and there was no difference between preoperative and postoperative swallowing functions. In this single-institutional preliminary study, we demonstrated that TORS is a feasible and safe treatment. A clinical multi-institutional study of TORS for laryngopharyngeal cancer has been approved as an advanced medical system study and is under way. In the near future, it is expected that the efficacy and safety of TORS for laryngopharyngeal cancer will be confirmed as the result of this multiple-institutional clinical study in Japan.